2010
DOI: 10.1186/1756-9966-29-79
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the expression of connexin26 in colorectal cancer

Abstract: BackgroundConnexin26 (Cx26) is one of the connexins (Cxs) family members which form gap junction channels. Cx26 is considered to be a tumor suppressor gene. However, recent studies revealed that over expression of Cx26 is associated with a poor prognosis in several human cancers. This study investigated the correlation between Cx26 expression and the clinicopathological features and P53 expression in colorectal cancer.MethodsOne hundred and fifty-three patients who underwent a curative resection were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Similarly recent studies tracking connexin levels as a cancer prognostic indicator produced a diverse set of outcomes. Over a dozen studies in the last decade correlate high connexin expression with a significantly better prognosis (e.g., Cx43 in prostate 39 , pancreatic 40 , breast 41 , head and neck SCC 42 , non-small-cell lung 43 , and colorectal 44 cancers; and Cx26 in colorectal 45 and intestinal type-gastric 46 cancers). In contrast, more than a dozen studies correlate high connexin expression with a poor prognosis (e.g., Cx43 in oral SCC 47 , esophageal SCC 48 and non-muscle invasive urothelial bladder cancer 49 ; and Cx26 in breast cancer 50,51 , lung SCC 52 , esophageal SCC 53 , colorectal cancer 37 and papillary and follicular thyroid cancer 54 ).…”
Section: Expression and Localizationmentioning
confidence: 99%
“…Similarly recent studies tracking connexin levels as a cancer prognostic indicator produced a diverse set of outcomes. Over a dozen studies in the last decade correlate high connexin expression with a significantly better prognosis (e.g., Cx43 in prostate 39 , pancreatic 40 , breast 41 , head and neck SCC 42 , non-small-cell lung 43 , and colorectal 44 cancers; and Cx26 in colorectal 45 and intestinal type-gastric 46 cancers). In contrast, more than a dozen studies correlate high connexin expression with a poor prognosis (e.g., Cx43 in oral SCC 47 , esophageal SCC 48 and non-muscle invasive urothelial bladder cancer 49 ; and Cx26 in breast cancer 50,51 , lung SCC 52 , esophageal SCC 53 , colorectal cancer 37 and papillary and follicular thyroid cancer 54 ).…”
Section: Expression and Localizationmentioning
confidence: 99%
“…We previously showed that reduced Cx26 protein levels were linked with improved prognosis after neoadjuvant chemotherapy where Cx32 protein detection had no prognostic impact [7]. Other studies came to the opposite conclusion by linking the loss of Cx26 expression to reduced survival in primary gastric and colorectal carcinomas [64], [65]. Therefore, Cx26 and Cx32 may not be stable markers and their prognostic relevance in cancer should be interpreted with particular care by considering tumor type, stage and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16 Cx26 was an independent prognostic factor according to their multivariate analysis. 16 Liu et al 17 assessed Cx26 expression in 205 gastric carcinoma cases, and their multivariate regression analysis revealed that positive Cx26 expression was an independent prognostic predictor of intestinal-type gastric carcinoma and indicated favourable prognosis.…”
Section: Connexin43 In Prostate Cancer G Benko Et Almentioning
confidence: 94%
“…Cx26 had a statistically significant relationship with disease recurrence and histological type. 16 The patients with Cx26-negative tumours had a significantly worse survival than those with positive tumours. 16 Cx26 was an independent prognostic factor according to their multivariate analysis.…”
Section: Connexin43 In Prostate Cancer G Benko Et Almentioning
confidence: 96%
See 1 more Smart Citation